Pemajemukan Kata Dalam Novel Hidden Figures Karya Margot Lee Shetterly - Rahmalia, Ana (PT. Alahyan Publisher Sukabumi, 2023)
Compounding is a word formation process in linguistics which aims to combine two or more morphemes to create new words and terms in a language. This study discusses about the compounding process in the novel Hidden Figures by Margot Lee Shetterly. The aims of this research is to describe the morphological process about compounding words and to show the changes in word form, meaning, and word class from this process. The method used in this research is a qualitative-descriptive research method with morphology as its approach. The data collection technique that used is the reading and notes technique. Data analysis techniques used include data condensation, data display, as well as drawing and verifying conclusions. The results of this study included 15 words that past a compounding process, 2 of them did not experience word class changes. However, the form and meaning of each word in general has changed.